Teaching in the age of covid-19:1 year later testmonials - Petar Jandrić, David Hayes, Paul Levinson, Line Lisberg Christensen, Happiness Onesmo Lukoko, Jimmy Ezekiel Kihwele, James Benedict Brown, Charles Reitz, Peter Mozelius, Harry G. Nejad, Ana Fuentes Martinez, Janine Aldous Arantes, Liz Jackson, Ulrika Gustafsson, Sandra Abegglen, Tom Burns, Sandra Sinfield, Michael Hogan, Pallavi Kishore, Paul R. Carr, Ivana Batarelo Kokić, Paul Prinsloo, Dennis Grauslund, Anne Steketee, Charlotte Achieng-Evensen, Blessing Funmi Komolafe, Juha Suoranta, Nina Hood, Marek Tesar, Jennifer Rose, Niklas Humble, James D. Kirylo, Julia Mañero, Lilia D. Monzó, Mikkel Lodahl, Jimmy Jaldemark, Susan M. Bridges, Navreeti Sharma, Jacob Davidsen, Jānis (John) Ozoliņš, Peter Bryant, Carlos Escaño, Jones Irwin, Kulpreet Kaur, Sarah Pfohl, Kevin Stockbridge, Thomas Ryberg, Olli Pyyhtinen, Suzanne SooHoo, Moses Kayode Hazzan, Jake Wright, Stephanie Hollings, Sonja Arndt, Andrew Gibbons, Shreya Urvashi, Daniella J. Forster, Ian Truelove, Peter Mayo, Glenn Rikowski, Paul Alexander Stewart, Michael Jopling, Georgina Tuari Stewart, Rachel Buchanan, Nesta Devine, Richa Shukla, Rene Novak, Madhav Mallya, Eva Biličić, Sean Sturm, Sahar D. Sattarzadeh, Abey P. Philip, Bridgette Redder, E. Jayne White, Derek R. Ford, Quaylan Allen, Mousumi Mukherjee & Sarah (Postdigital science and education article, 2024)
A research paper submitted to the Post digital Science and education journal, Volume 3, pages 1073–1223, (2021